PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN HOLTIKULTURA DAN PETERNAKAN KABUPATEN PASAMAN BARAT - Mirtha Mirtha; Yasri Hasim (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
The aim of this research are to analyze: 1) influence of leadership toward the work enviroment, 2) influence of leadership toward the work satisfaction, 3) the effect of the work enviroment on the work satisfaction, 4) the influence of leadership toward the work discipline, 5) the impact of leadership toward the work discipline and 6) the impact of work enviroment on the work discipline. Kinds of this research is causative descriptive research. Population is all employees (46 persons) in Dinas Pertanian Tanaman Pangan Holtikultura dan Peternakanof Pasaman Barat Region. Sampling method is stratified propotional random sampling so that were selected 41 employees as the respondence. Descriptive analisys , analisys rule and regulation test and path analisys were used answer the research problem. Result this research proved that 1) leadership hassignificant influences toward the work enviroment, 2)leadership hasn’t signifcant influence toward the work satisfaction,3) work enviroment hasn’t significant influence toward the work satisfaction, 4) leadershiphas significant influence toward the work motivation, 5)work  enviromenthas  significant influence toward the workmotivation, and 6) work satisfaction has significant influence toward the workmotivation. Keywords: Leadership, Work Enviroment, Work Satisfaction, Work Motivation